The Effect of Teamwork and Communication on Employee Productivity of LNG Badak Bontang Hospital - Ihwan Agus; Felasa Andriyana (Universitas Muhammadiyah Palu, 2025)
This research aims to determine the effect of teamwork and communication on employee productivity at Badak Bontang LNG Hospital. This research method is descriptive-quantitative, using data collection techniques such as observation, documentation, questionnaires and interviews. The population in this study were employees of the Badak Bontang LNG Hospital with a sample size of 65 respondents. The analysis technique used is multiple linear regression with the SPSS version 16 application. The results of the research show that from the results of the partial test or T test on collaboration time, results are tcount 12.723 > ttable 1.998 and Communication are tcount 7.620 > ttable 1.998 with a significance of 0.00 < 0, 05. The results of the simultaneous test or Ftest in this study obtained Fcount of 82.835 > Ftable 3.15 with a significance of 0.00 < 0.05. From the results of the T Test and F Test, it is known that the Collaboration and Communication Team has a partial and significant effect on the productivity of Badak Bontang LNG Hospital employees